The Application of Multi‑Criteria Taxonomy to Comparative Analysis of Structures of Sustainable Development - Cheba, Katarzyna; Bąk, Iwona Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
One of the most common errors in research on sustainable development is to analyse a set of features describing this development within one set of diagnostic features. Such an approach does not allow for examining the real changes taking place within each area of sustainable development. These changes may have a completely different direction in the case of indicators describing, for example, the economic area or the environmental area of sustainable development. The solution is to consider the indicators separately for each area and then compare the results obtained. In this work, multi‑criteria taxonomy was used for this purpose. The study used indicators published by Eurostat to monitor progress in implementing the Agenda for Sustainable Development 2030 from 2008 and 2016. The results presented in the paper confirmed the considerable diversity of the EU countries in each area of sustainable development and their large heterogeneity.